2017
DOI: 10.1186/s13023-017-0708-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of TECTA mutation in patients with mid-frequency sensorineural hearing loss

Abstract: BackgroundTo date, 102 genes have been reported as responsible for non-syndromic hearing loss, some of which are associated with specific audiogram features. Four genes have been reported as causative for mid-frequency sensorineural hearing loss (MFSNHL), among which TECTA is the most frequently reported; however, the prevalence of TECTA mutations is unknown. To elucidate the prevalence of TECTA mutation in MFSNHL and clarify genotype-phenotype correlations, we analyzed the genetic and clinical features of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Among those genes, mutations in TECTA are the most frequent cause of mid-frequency HL [1,24,33,34]. Yamamoto et al reported that pathogenic and possibly pathogenic variants of TECTA were found in 6.0% of mid-frequency SNHL patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…Among those genes, mutations in TECTA are the most frequent cause of mid-frequency HL [1,24,33,34]. Yamamoto et al reported that pathogenic and possibly pathogenic variants of TECTA were found in 6.0% of mid-frequency SNHL patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…Deafness genes were tested at the Laboratory of Auditory Disorders, National Institute of Sensory Organs, National Tokyo Medical Center by the Sanger method using the genomic DNA extracted from patients' peripheral blood cells when their deafness genes have not been clarified by previous genetic testing performed by BML supported by National Health Insurance. We performed the Sanger methods as previously reported . Genes and mutations of the enrolled patients are shown in Supplementary Table I.…”
Section: Methodsmentioning
confidence: 99%
“…We performed the Sanger methods as previously reported. 15,34,35 Genes and mutations of the enrolled patients are shown in Supplementary Table I.…”
Section: Enrolled Patientsmentioning
confidence: 99%
“…TECTA can be responsible for autosomal dominant or autosomal recessive hearing loss. Among families with dominant hearing loss, missense mutations in the TECTA zonadhesion domain (amino acid residues 260‐1694) are associated with high‐frequency hearing loss, while missense mutations in the TECTA zona pellucida domain (residues 1795‐2059) are associated with mid‐frequency hearing impairment 35‐37 . This correspondence obtains for family HL277 (p.Ala963Thr) and family DF193 (p.Asp2006Gly) (Figure S1).…”
Section: Resultsmentioning
confidence: 76%